Information, Knowledge, and Behavior : Evaluating Alternative Methods of Delivering School Information to Parents - Cerdan-Infantes, Pedro; Filmer, Deon; Santoso (University of Chicago Press, 2022)
This paper evaluates alternative approaches to disseminating information about a school-based management program in Indonesia. Low-intensity approaches, sending a letter from the principal or a colorful pamphlet home with the child, had no impact. Holding a facilitated meeting with school stakeholders or sending targeted text messages (SMSs) to parents increased knowledge and participation. Facilitated meetings increased overall knowledge, fostered a feeling of transparency, and increased participation in formal channels for providing feedback to the school. SMSs increased knowledge about specific aspects of the program, such as the grant amount, and increased participation through informal channels.